Differences Between Omnivores and Vegetarians in Personality Profiles, Values, and Empathy: A Systematic Review - Holler, Sophie; Cramer, Holger; Liebscher, Daniela; Jeitler, Michael; Schumann, Dania; Murthy, Vijayendra; Michalsen, Andreas; Kessler, Christian S. (Frontiers in Psychology, 2021)
Numerous medical studies have documented vegetarian diets as having various health benefits. Studies have also compared vegetarians with other dietary groups from a socio-psychological perspective. The objective of this review is to investigate the differences between vegetarians and omnivores in terms of their personality profiles, values, and empathy skills. A search was conducted across three electronic databases. Non-randomized, observational, cross-sectional, and cohort studies were eligible. Outcomes provided information about the differences between the above-mentioned dietary groups regarding their personality profiles, values, and empathy skills. A shortened version of the Newcastle–Ottawa Scale was used to assess the risk of bias for the included studies. Of the 2,513 different studies found, 25 (total number of participants n = 23,589) were ultimately included. These studies indicate that vegetarians significantly differ from omnivores in their personalities, values, and ability to be empathetic. Omnivorism is associated with an increased orientation toward social dominance, greater right-wing authoritarianism, and, in line with this, a stronger tendency to be prejudiced. Vegetarianism is associated with greater openness and empathy. The values of vegetarians are based more on universalism, hedonism, stimulation, and self-direction, whereas the values of omnivores are based more on the idea of power. To answer a narrowly defined and clear question, issues such as animal ethics, animal rights, and environmental protection are not considered in this review. The findings of this review, showing marked differences in personality correlating to the choice of diet and the increasing influence of plant-based diets on a global level, indicate that further studies about vegetarianism are warranted.